Klute [videorecording (DVD)] - Pakula, Alan J., 1928-1998; Pakula, Alan J., 1928-1998; Fonda, Jane, 1937-; Sutherland, Donald, 1935-; Cioffi, Charles, 1935-; Scheider, Roy (Warner Bros. Pictures ; Distributed by Warner Home Video, 2002)
Enigmatic small town Detective John Klute is hired to track down his best friend, a research scientist who has disappeared without a trace. His investigation leads him to New York City, and Bree Daniels, skilled, intelligent, cynical, and personally troubled part-time model and full-time call girl. She was savagely beaten once by a man from Pennsylvania, who may have been his friend. Taking a journey into the underbelly of the Big Apple the two begin to realize that everything and everyone may not be what they seem. Dangers lurk in the shadows, old habits become harder to break, and love is a four-letter word best left unspoken for two people from two very different worlds.